2015
DOI: 10.1002/jssc.201500834
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of chiral stationary phases based on cinchona alkaloids bonded to crown ethers by chiral modification

Abstract: To improve the chiral recognition capability of a cinchona alkaloid crown ether chiral stationary phase, the crown ether moiety was modified by the chiral group of (1S, 2S)-2-aminocyclohexyl phenylcarbamate. Both quinine and quinidine-based stationary phases were evaluated by chiral acids, chiral primary amines and amino acids. The quinine/quinidine and crown ether provided ion-exchange sites and complex interaction site for carboxyl group and primary amine group in amino acids, respectively, which were necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…For example, it was shown that surface proximity as well as sophisticated linker chemistry may significantly improve enantioselectivity [4][5][6][7]. Since the development of Cinchona carbamate type anion exchangers [8], several studies focused on the systematic optimization of the selector structure have been performed [9][10][11][12][13][14][15], including research focused on different anchoring strategies [4,16,17]. Importantly, longer retention times and slightly enhanced enantioselectivity were achieved by attaching the selector by the carbamoyl unit double bond, in comparison to the selector of a similar structure bonded by the cinchonan double bond.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown that surface proximity as well as sophisticated linker chemistry may significantly improve enantioselectivity [4][5][6][7]. Since the development of Cinchona carbamate type anion exchangers [8], several studies focused on the systematic optimization of the selector structure have been performed [9][10][11][12][13][14][15], including research focused on different anchoring strategies [4,16,17]. Importantly, longer retention times and slightly enhanced enantioselectivity were achieved by attaching the selector by the carbamoyl unit double bond, in comparison to the selector of a similar structure bonded by the cinchonan double bond.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also drew attention to the essential role of the chiral environment in the crown ether ring [ 29 ]. Adding an additional (1 S ,2 S )-2-aminocyclohexyl phenylcarbamate (Heca) chiral group to the Cinchona alkaloid crown ether chiral selector ( Figure 4 , right) resulted in improved chiral recognition of the primary amine enantiomers.…”
Section: Recent Applications Of Crown Ether-based Cspsmentioning
confidence: 99%
“…The results underlined the importance of the distance of the chiral center from the acridine ring, which was found to be decisive for the efficiency of enantiomeric recognition. Another study also drew attention to the essential role of the chiral environment in the crown ether ring [29]. Adding an additional (1 S,2 S)-2-aminocyclohexyl phenylcarbamate (Heca) chiral group to the Cinchona alkaloid crown ether chiral selector (Figure 4, right) resulted in improved chiral recognition of the primary amine enantiomers.…”
Section: Columnmentioning
confidence: 99%
“…[3] (3,3'-Diphenyl-1,1-binaphthyl)-20crown-6, [4][5][6][7][8] (+)-(18-crown-6)-2,3,11,12-tetracarboxylic acid, [9,10] and phenolic pseudo chiral crown ethers [11,12] are the most effective CSPs of the crown ether type. [13] A series of CSPs based on immobilized chiral crown ethers [(+)-18-crown-6 tetracarboxylic acid] and (3,3-diphenyl-1,1-binaphthyl)-20-crown-6 on polystyrene or silica gel showed good resolution ability for α-amino acids and their derivatives. [14][15][16][17][18][19][20][21] The related commercialized CSP known as CROWNPAK CR(+) (Daicel Chemical Industries) has proven to be useful for the chromatographic resolution of chiral compounds that contain a primary amino group.…”
Section: Introductionmentioning
confidence: 99%
“…H NMR and13 C NMR spectra were obtained with a Varian Mercury Plus 300 and a Unity-Inova 500 spectrometer. Scanning electron microscopy (SEM) images were recorded on an FEI Quanta FEG 650 scanning electron microscope (USA).…”
mentioning
confidence: 99%